Find all pairs of integer solutions satisfying x 2 ( y − 1 ) + y 2 ( x − 1 ) = 1
If the solutions can be represented in the form ( x i , y i ) where i = 1 , 2 , … , n i.e n solutions are there then find : i = 1 ∑ n ( x i + y i )
Explicit example : If the solutions are ( 0 , 2 ) & ( 2 , 3 ) then you need to compute 0 + 2 + 2 + 3 = 7 and enter 7 as answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, use distributive and factor into: x 2 y + y 2 x = x 2 + y 2 + 1 → x y ( x + y ) = ( x + y ) 2 − 2 x y + 1 → x y ( x + y + 2 ) = ( x + y ) 2 + 1 . Let s = x + y and t = x y we get t ( s + 2 ) = s 2 + 1 . Now, since neither x = 0 nor y = 0 give integer solutions, t = 0 . So we see that s + 2 ∣ s 2 + 1 = ( s + 2 − 2 ) 2 + 1 = ( s + 2 ) 2 − 4 ( s + 2 ) + 5 → s + 2 ∣ 5 . The last equation gives four answers, since 5 is prime, that are { 3 , − 3 , − 1 , − 7 } . Now we have the pairs ( s , t ) ∈ { ( 3 , 2 ) , ( − 3 , − 1 0 ) , ( − 1 , 2 ) , ( − 7 , − 1 0 ) } . Notice that x and y must solve the equation z 2 − s z + t = 0 , meaning Δ = s 2 − 4 t ≥ 0 and, since they are integers, Δ must be a perfect square, which the least two pairs don't do. So, we must have ( s , t ) ∈ { ( 3 , 2 ) , ( − 3 , − 1 0 ) } , therefore the sum in the problem must be 0 . We should've doubled the result, accounting for the symmetry on the variables, but it's the same. For completeness, ( x , y ) ∈ { ( 1 , 2 ) , ( 2 , 1 ) , ( 2 , − 5 ) , ( − 5 , 2 ) }
Problem Loading...
Note Loading...
Set Loading...
Set x = u + 1 , y = v + 1 which leads to the equation ( u v + 1 ) ( u + v + 4 ) = 5
Now here the factors are either equal to 5 or − 5 , which leads to four set of simultaneous equations of which only two are solvabe and they are,
{ u + v = 1 u v = 0 & { u + v = − 5 u v = − 6
Hence ( x , y ) = ( u + 1 , v + 1 ) = ( 1 , 2 ) , ( 2 , 1 ) , ( − 5 , 2 ) , ( 2 , − 5 ) & the answer is 0